Empowering Women Farmers Through Technology: Potato Chip Production Enhancement in Sedaeng Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Sedaeng Village in Pasuruan Regency, East Java, is characterized by fertile agricultural land and a strong culture of community participation. Among its local initiatives, the Dewi Sri Rejeki Women Farmers Group (Kelompok Wanita Tani – KWT), comprising 14 members, has long produced potato chips using traditional methods. However, the absence of standardized processing technology and limited managerial skills has hindered production efficiency, consistency, and marketing reach. To address these challenges, a Community Partnership Program (PKM) was implemented to empower the group through appropriate technology transfer, entrepreneurship training, and digital marketing development. The intervention introduced a semi-automatic potato slicer and an oil-spinner machine, improved packaging and labeling, and strengthened members’ capacity in business management and financial recording. The program applied a participatory and educational approach, combining technical demonstrations, workshops, and mentoring sessions to ensure active involvement and skill adoption. Quantitative results indicated a substantial improvement in production performance: slicing and draining time was reduced by 65 percent, oil content declined from 25 to 10 percent, and production output increased by approximately 60 percent, from 50–60 to 90–100 packs per week. Qualitatively, members demonstrated stronger entrepreneurial motivation, better coordination, and greater confidence in expanding their market reach through digital platforms. The outcomes highlight the effectiveness of combining technology adoption, managerial empowerment, and marketing innovation in strengthening rural women’s economic independence. This PKM initiative not only enhanced the productivity and competitiveness of Sedaeng’s women farmers but also serves as a replicable model for sustainable community-based agroindustry development in similar rural contexts.